2016
DOI: 10.22365/jpsych.2016.273.204
|View full text |Cite
|
Sign up to set email alerts
|

There is no safe threshold for lead exposure: Α literature review

Abstract: L ead was one of the most dangerous environmental toxic substances for a long time in western countries, and this is still the case for many places on earth today. Its neurotoxic potential is highly significant but its secure blood level concentration remains unknown. The aim of this study was to approach the above issue from the perspective of social psychiatry. A systematic search was made of Dialog and Datastar interfaces for data regarding the neuropsychiatric complications of direct or chronic exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 71 publications
(64 reference statements)
2
76
0
4
Order By: Relevance
“…25 At the same time, with reference to the level of 'lead toxicity' in children, ACCLPP eliminated the term 'level of concern' for blood lead level (previously defined as 10 μg/dL) and replaced it with a reference level of 5 μg/dL, based on the 97.5th percentile of the population blood lead level in children aged between 1 and 5 years. 2,13,24 This was supported by the American Academy of Pediatrics who acknowledged that even the lowest degree of lead exposure might harm children, 13,23,26 and echoed the European Food Safety Authority who concluded that there is no known safe exposure to lead as evidenced by international studies in Europe. [27][28][29] In other words, there is no safe or 'non-toxic' blood lead level.…”
Section: Potential Public Health Implicationsmentioning
confidence: 99%
“…25 At the same time, with reference to the level of 'lead toxicity' in children, ACCLPP eliminated the term 'level of concern' for blood lead level (previously defined as 10 μg/dL) and replaced it with a reference level of 5 μg/dL, based on the 97.5th percentile of the population blood lead level in children aged between 1 and 5 years. 2,13,24 This was supported by the American Academy of Pediatrics who acknowledged that even the lowest degree of lead exposure might harm children, 13,23,26 and echoed the European Food Safety Authority who concluded that there is no known safe exposure to lead as evidenced by international studies in Europe. [27][28][29] In other words, there is no safe or 'non-toxic' blood lead level.…”
Section: Potential Public Health Implicationsmentioning
confidence: 99%
“…Alarmingly, early-life Pb exposure even in trace amounts induces neurobehavioral manifestations that may not be evident until later in life (Vorvolakos et al, 2016). They include hyperactivity, cognitive deficits and altered responses to drugs of abuse including EtOH.…”
Section: Lead Ethanol and The Two Faces Of Reinforcementmentioning
confidence: 99%
“…These include diseases affecting the central nervous system, trauma, diseases affecting the peripheral nervous system and diseases or trauma affecting the muscle and tendon. Many reasons have been reported such as ganglion cyst in the proximal tibiofibular joint [3], motor cortex contusion [4], long-term lead intoxication [5], tight application of compression bandage [6,7], after lateral decubitus position [8] following dislocation reduction after total hip arthroplasty and gluteal haematoma [9,10], a complication of disc surgery [11], peripheral nerve entrapment [12,13], poorly administered injections (14], sciatic nerve pressure, piriformis syndrome [15], knee dislocations [16], following spinal and spinoepidural anaesthesia [17], paraspinal abscess [18], myopathies [19], neuropathic demyelinisation, hereditary neuropathies [20], popliteal artery aneurism [21], stroke [22,23], neuromuscular diseases [24,25], degenerative lumbar spinal diseases [26], gluteal compartment syndrome [27], decompression in burns [28], parasitic diseases such as neuro schistomiasis [29], after lower extremity compartment syndrome [30], and after total knee prosthesis [31].…”
Section: Introductionmentioning
confidence: 99%